Challenges and Opportunities for the Large-Scale Chemoenzymatic Glycoengineering of Therapeutic N-Glycosylated Monoclonal Antibodies - Ivanova, Adelina; Falcioni, Francesco (Frontiers in Catalysis, 2022)
Variability in the glycosylation profile of therapeutic monoclonal antibodies (mAbs), due to recombinant production technologies, leads to inconsistencies in effector functions and pharmacokinetic properties, both batch-to-batch and within single batches. It also poses regulatory concerns over the effectiveness of commercially available formulations. In vitro chemoenzymatic glycoengineering of variants displaying a homogeneous glycan profile is a trending strategy for ensuring consistent, controlled, and enhanced therapeutic performance, but reported successes are largely limited to small-scale applications. The major challenges for the industrial-scale introduction of the technique stem from the need for activated sugar donors, which can participate in undesired side reactions, and from the economic cost of the additional enzymatic steps and purification stages. While recent developments within the area address some of these obstacles, it appears that more effort is required in order to access the untapped potential of biocatalysis to enable the robust production of therapeutically superior constructs.